Anhelli by Juliusz Słowacki. A Story of Sadness and Death - Ciechańska, Magdalena (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
The article includs an interpretation of „Anhelli”, the poem by Juliusz Słowacki and his subsequent lyricthat begins with the words: „I wstał Anhelli… z grobu… za nim wszystkie duchy…”. The analysis ofboth works is focused on the issues of death (physical and mental /emotional), sadness, lack of hope,revival and resurrection. The aim of this article is to present images of the suffering and dying of thepoem’s characters and the degree of their initiation into the death. An important point of the poem’sinterpretation is a description of the place of action — Siberia, which is called the Land of Graves. Veryimportant is also the analysis of the end of the poem and its comparison with the subsequent lyric, andthe relation of the second work with the philosophy of the last period of Juliusz Słowacki’s output.